THE ROLE OF INTERPERSONAL COMMUNICATION ON LEARNING MOTIVATION IN JUNIOR HIGH SCHOOL STUDENTS 37 MEDAN IS MEDIATED BY STUDENT ENGANGEMENT - Rofi Dwi Putri Ramadhani; Salamiah Sari Dewi; Patisina Patisina (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to explore the dynamics of the relationship between interpersonal communication and student engagement in shaping learning motivation. A quantitative research method was employed to analyze the data. In this study, the sample consisted of 190 participants. The results show that interpersonal communication has a positive and significant effect on learning motivation. This is indicated by a coefficient value of 0.653, a t-statistic of 7.889 (> 1.653), and a p-value of 0.000 (< 0.05). Interpersonal communication also has a positive and significant effect on student engagement, as shown by a coefficient value of 0.650, a t-statistic of 9.077 (> 1.653), and a p-value of 0.000 (< 0.05). Student engagement, in turn, has a positive and significant effect on learning motivation. With a coefficient of 0.662, a t-statistic of 9.502 (> 1.653), and a p-value of 0.000 (< 0.05), it is evident that student involvement in the learning process plays an important role in enhancing learning motivation. Active student engagement enables learners to feel a stronger sense of purpose and drive in their academic pursuits. Furthermore, student engagement partially mediates the effect of interpersonal communication on learning motivation. The direct effect of interpersonal communication on learning motivation is greater (58.4%) compared to the indirect effect through student engagement (43.1%). This indicates that although student engagement serves as a mediator, the direct influence of interpersonal communication remains dominant.